PENGARUH ORIENTASI ETIKA, KOMITMEN PROFESIONAL DAN BUDAYA ETIS ORGANISASI TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI MELALUI RASIONALISASI SEBAGAI VARIABEL MODERATING (Studi Empiris Pada Bank Bumn Dan Bank Bumd Di Kota Pekanbaru) - Fauzalina Triani Fauzi; Yusralaini Yusralaini; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted to examine the effect of variable Orientation of Idealism ethics and relativism, professional commitment and ethical culture of the organization on the the tendency of accounting fraud with rationalization as a moderation variable On State And Local Banks In Pekanbaru City. Collecting data using questionnaires. This research data is obtained from head of unit of credit of effort of people. Of the 78 questionnaires distributed, the number returned was 74 questionnaires. Data were analyzed by using Moderated Regresion Analysis with the help of computer program SPSS version 24.0. The results showed that ethical orientation of idealism, ethical orientation of relativism, professional commitment and organizational ethical culture influenced the tendency of accounting fraud. Rationalization moderates the influence of the ethical orientation of relativism and the ethical culture of the organization on the tendency of accounting fraud. Rationalization does not moderate the influence of ethical orientation of idealism and professional commitment to the tendency of accounting fraud.Keywords: Ethics Orientations, Professional Commitments, Ethical Cultural Organization, Tendency Of Accounting Fraud, and Rationalization